The Willingness to Pay for Vaccination against Tick-borne Encephalitis and Implications for Public Health Policy: Evidence from Sweden - Slunge, Daniel (University of Gothenburg, 2015)
The study estimates the willingness to pay (WTP) for TBE vaccination and the effect of a possible TBE vaccine subsidy on vaccination rates in Sweden. We also estimate the current vaccination coverage in areas differing in TBE incidence and analyze the role of income, risk behavior and other factors influencing vaccine demand.

Purpose:

To estimate the willingness to pay (WTP) for TBE vaccination and the effect of a possible TBE vaccine subsidy on vaccination rates in Sweden.

The data set contains the variables used in the study The Willingness to Pay for Vaccination against Tick-borne Encephalitis and Implications for Public Health Policy: Evidence from Sweden, published in PLOS ONE. The survey on Ticks, TBE and Lyme Disease contains additional questions not included in this dataset. The dataset are available for direct download in SPSS and Excel format.

Studien undersöker betalningsviljan för TBE vaccin, vaccinationsgrad, vilka som vaccinerar sig vid gällande marknadspriser och effekten av en möjlig vaccinsubvention.

Syfte:

Att undersöka betalningsviljan för TBE vaccin , vaccinationsgrad, vilka som vaccinerar sig vid gällande marknadspriser och effekten av en möjlig vaccinsubvention.

Datasetet innehåller de variabler som använts i studien "The Willingness to Pay for Vaccination against Tick-borne Encephalitis and Implications for Public Health Policy: Evidence from Sweden", som publicerats i PLOS ONE. Enkäten om fästingar, TBE och Borrelia innehåller ytterligare frågor som inte ingår i detta underlag. Data finns tillgängligt för nedladdning i SPSS och - Excel format.
Betalningsvilja för vaccin mot TBE (fästingburen encefalit) och konsekvenser för hälsopolitik
Keywords: subsidies; bidrag; Vaccination; Vaccination; Health Policy; Hälso- och sjukvårdspolitik; Ticks; Fästingar; Tick-Borne Diseases; Fästingburna sjukdomar; Encephalitis Viruses, Tick-Borne; Encefalitvirus, fästingburen; vaccine; vaccin; willingness to pay; betalningsvilja; stated preference; angiven preferens; contingent valuation; kontingent värdering; TBE; TBE; HEALTH; HÄLSA; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Medical and Health Sciences; Medicin och hälsovetenskap